2011
DOI: 10.3109/09638288.2010.549288
|View full text |Cite
|
Sign up to set email alerts
|

Specific treatment of Prader–Willi syndrome through cyclical rehabilitation programmes

Abstract: A multidisciplinary approach and a daily calorie-counted diet can lead to significant weight loss in teenage and adult PWS patients. This approach would also be suitable in treating patients with other obesity syndromes with mental retardation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 34 publications
4
54
0
4
Order By: Relevance
“…In a patient cohort trained at our institute we observed that muscular mass did not increase after training in a normal dietary regimen (2). Muscle mass loss in PW patients has been pointed out by others (1,22) and contributes to alterations in motor performance that leads to obesity and severe disabilities.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a patient cohort trained at our institute we observed that muscular mass did not increase after training in a normal dietary regimen (2). Muscle mass loss in PW patients has been pointed out by others (1,22) and contributes to alterations in motor performance that leads to obesity and severe disabilities.…”
Section: Discussionmentioning
confidence: 86%
“…Physical rehabilitation is commonly used to improve skeletal mass performance and to control obesity of adult PW patients. A retrospective analysis of a PW patient cohort, trained at our institute, showed that intense physical exercise programs have beneficial effects on body weight, but do not improve muscle mass of patients, despite normal calories intake (2). Our data suggested that the regulation of muscle mass was defective in PW patients.…”
Section: Introductionmentioning
confidence: 78%
“…Subsequently compliance and weight management improved. The authors concluded that: activities have to be widely mixed with appropriate rest times, since fatigue and stress can provoke temper tantrums; definitive progress was achieved following the introduction of psychomotor activity and music therapy; groups of more than ten patients would be hard to manage due to the complicated social dynamics; and activities were performed at a lower speed than normal and with frequent interruptions (Grolla et al, 2011). Miller et al (2013) also recommended daily moderate exercise to the 63 individuals with PWS who participated in their study, but paid particular attention to the effects of a balanced diet in PWS.…”
Section: Management Of Hyperphagia In Pwsmentioning
confidence: 98%
“…Grolla et al (2011) evaluated a physical training program for weight management in PWS adults in a residential care setting. The program took place four times a year, each lasting for four weeks.…”
Section: Management Of Hyperphagia In Pwsmentioning
confidence: 99%
“…The severity of the obesity can be managed by early diagnosis, diet restrictions, controlling access to food and tailored exercise programmes (Sinnema et al, 2011b). However, weight control by strictly restricting calorific intake may lead to physiological and psychological stress (Dykens et al, 2011;Grolla et al, 2011). Grolla and colleagues (2011) have reported successful weight loss and weight control by exercise and physical therapies without strict dietary restrictions.…”
Section: Theoretical Explanations For Hyperphagiamentioning
confidence: 99%